Investing in agricultural water management to benefit smallholder farmers in Madhya Pradesh, India. - Evans, Alexandra E.V.; Giordano, Meredith A.; Clayton, Terry (International Water Management Institute, 2012)
This Working Paper summarizes research conducted as part of the AgWater Solutions Project in the State of Madhya Pradesh, India, from 2009 to 2012. Agriculture accounts for 21% of the gross domestic product (GDP) of Madhya Pradesh and state agriculture contributes substantially to India?s total annual wheat, pulses and soybean production. While the incidence of poverty has declined, it remains well above the national average of 21%. Researchers from the AgWater Solutions Project explored rainwater harvesting, drip irrigation and how investors might leverage the Mahatma Gandhi National Rural Employment Guarantee Scheme (MGNREGS). Research methodologies included rapid rural appraisals, interviews, survey questionnaires and literature reviews. The main findings indicate that: 1) small private rainwater harvesting structures would increase farm incomes, but development requires more flexible financing options for smallholder farmers; 2) replacing the current subsidy system with interest-free loans would be cheaper for the government, give farmers more choice and stimulate private sector innovation in drip irrigation; and 3) farmers would like more involvement in the decision-making processes of the MGNREGS, which already funds thousands of agricultural water management structures every year. Soft loans and pump rental markets for water-lifting and distribution systems would stimulate further development.